Integration of Zero Waste Concept and MUI Fatwa in Waste Management Based on Maqasid al-Syari'ah - Khalid Karim; Faqih Abdul Matin; Aida Humaira; Daud Lintang (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article examines the integration of the Zero Waste concept with the Indonesian Ulema Council (MUI) fatwa on waste management within the framework of maqasid al-syari'ah. Indonesia's waste crisis marked by rising generation volumes, over-reliance on final disposal sites, and low community behavioral change demands a preventive, value based paradigm beyond purely technical solutions. Using a qualitative library research method with normative-conceptual analysis, this study finds that the principles of Zero Waste are substantively consistent with Islamic environmental ethics embedded in the MUI fatwa, particularly hifz al-bi'ah (environmental preservation), the prohibition of israf (extravagance) and ifsad (corruption of nature), and the affirmation of collective communal responsibility. The MUI fatwa functions as a normative instrument that strengthens social legitimacy and drives behavioral change toward sustainable waste management. This integration offers a strategic approach for reinforcing waste-management policy, public education, and the formation of a religiously-grounded environmental culture in Indonesia.